Chitinase-like proteins promoting tumorigenesis through disruption of cell polarity via enlarged endosomal vesicles - Khalili, Dilan; Kunc, Martin; Herbrich, Sarah; Müller, Anna M.; Theopold, Ulrich (Frontiers in Oncology, 2023)
Chitinase-like proteins (CLPs) are associated with tissue-remodeling and inflammation but also with several disorders, including fibrosis, atherosclerosis, allergies, and cancer. However, CLP's role in tumors is far from clear. Here, we utilize the fruitfly Drosophila melanogaster to investigate the function of CLPs (imaginal disc growth factors; Idgf's) in RasV12 dysplastic salivary glands. We find one of the Idgf's members, Idgf3, is transcriptionally induced in a JNK-dependent manner via a positive feedback loop mediated by reactive oxygen species (ROS). Moreover, Idgf3 accumulates in enlarged endosomal vesicles (EnVs) that promote tumor progression by disrupting cytoskeletal organization. The process is mediated via the downstream component, αSpectrin, which localizes to the EnVs. We observe similar phenotypes upon expression of human CLP members in our fly model indicating phylogenetic conservation. Our data provide new insight into CLP function in tumors and identify specific targets for tumor control.